APPLICATION OF ARTIFICIAL INTELLIGENCE FOR SOFTWARE TESTING AUTOMATION - Гуральник, Фредерік (SWorldJournal, 2024)
This paper examines the theoretical aspects of applying artificial intelligence (AI) to automate software testing. Given the rapidly increasing complexity of software systems and the need to accelerate development cycles, test automation has become criti